LED lighting threatens adult aquatic insects: Impact magnitude and distance thresholds - Deborah Carannante (Wiley, 2021)
Abstract Artificial light at night (ALAN) is increasing globally, and changing in quality due to the installation of white LED street lighting. ALAN is a threat to biodiversity and ecosystem functioning, yet important knowledge gaps exist regarding the magnitude of impacts and how these vary between habitats and levels of exposure. The disturbance of aquatic habitats by ALAN is of particular concern as human settlements and activities are often located near waterbodies, and many aquatic species are sensitive to ALAN. Focusing on adult aquatic insects, an experimental approach was employed in the riparian zone of a structurally simplified river within a dark rural landscape. Two studies were used to (a) estimate the magnitude of the capture effect of white LED lamps and (b) to explore how captures at lamps vary with their distance from the river, and define any distance thresholds. Both studies sampled mayflies (Ephemeroptera), caddisflies (Trichoptera) and true flies (Diptera) repeatedly during mid‐to‐late summer using modified flight intercept traps positioned adjacent to portable LED lamps. In Study A, lit traps were paired with unlit controls. In Study B, lit traps were positioned at six distances up to a maximum of 80 m from the stream edge. For each of the three study orders, captures were significantly higher in the lit treatment compared to the dark control, with medium to large effect sizes. For all study orders, captures at lamps significantly reduced with increasing distance from the river edge. Rapid declines in captures were recorded for Trichoptera (from 10 m) and Ephemeroptera (40 m), with a more gradual decline in Diptera from 60 m that continued up to the maximum sample distance. Previous research indicates that LED lighting can be less attractive to flying insects than broader spectrum alternatives. However, this study demonstrates that the effects of white LED lamps on flying adult aquatic insects should not be dismissed and can extend far from aquatic habitats. As a precautionary approach, and until finer recommendations are available, we recommend that LED lamps should be excluded from a buffer zone of ca. 40–60 m around rivers.